Table of contents and editorial information for Vol. 24, no. 2, Spring 1997 - G. Daniel Harden (Educational Considerations, 1997)
Table of contents and editorial information for Vol. 24, no. 2, Spring 1997, Educational Considerations: theme issue "Social Foundations and Philosophy of Education."